Tenure and Due Process - Joseph L. Mills; A. Bruce Hartung (Educational Considerations, 1974)
The legal significance of tenure is reviewed in this article as it relates to the new and developing laws of due process. The authors suggest that "expectancy of re-employment" may become a new form of property right.